Renato Rosaldo: Ensayos en antropología crítica Rodrigo Díaz Cruz (ed.) - Hernández Castillo, Rosalva Aida (Alteridades, 2014)
Reseña del libro de Rodrigo Díaz Cruz (ed.), Renato Rosaldo: Ensayos en antropología crítica, Casa Juan Pablos/Fundación Rockefeller/Universidad Autónoma Metropolitana-Iztapalapa (col. Estudios Transnacionales), México, 2006.